Thoughts on Education in the Works of Abdullah Avloni - Qalandar Rustamov (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
About Avloni's life and work is provided in the school textbook. This article provides additional information about Avloni. This information will help to reveal more about the life and work of the great scholar of Uzbek literature - Avloni, his pedagogical activity, his contribution to literature.